2019
DOI: 10.1111/1348-0421.12759
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the subgingival microbiota in periodontitis patients: Comparison of the surface layer and the underlying layers

Abstract: Periodontitis is a major cause of tooth loss in adults that initially results from dental plaque. Subgingival plaque pathogenesis is affected by both community composition and plaque structures, although limited data are available concerning the latter. To bridge this knowledge gap, subgingival plaques were obtained using filter paper (the fourth layer) and curette (the first-third layers) sequentially and the phylogenetic differences between the first-third layers and the fourth layer were characterized by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…Furthermore, we described the variation of microbial composition in different PPDs. Our results showed that some pathobionts were consistent with those reported in previous studies (Kirst et al, 2015;Liu et al, 2020) and supported the finding that periodontal dysbiosis was not due to specific microorganisms, rather due to the increasing level of pathobionts. The two reasons for this are likely that (1) microbial community dysbiosis leads to periodontal disease, and (2) periodontitis is caused by some specific pathogenic bacteria that have not yet been identified.…”
Section: Overall Reviewsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, we described the variation of microbial composition in different PPDs. Our results showed that some pathobionts were consistent with those reported in previous studies (Kirst et al, 2015;Liu et al, 2020) and supported the finding that periodontal dysbiosis was not due to specific microorganisms, rather due to the increasing level of pathobionts. The two reasons for this are likely that (1) microbial community dysbiosis leads to periodontal disease, and (2) periodontitis is caused by some specific pathogenic bacteria that have not yet been identified.…”
Section: Overall Reviewsupporting
confidence: 93%
“…The datasets from nine publications (Griffen et al, 2012;Galimanas et al, 2014;Bizzarro et al, 2016;Califf et al, 2017;Chen et al, 2018;Peŕez-Chaparro et al, 2018;Wei et al, 2019;Liu et al, 2020;Shi et al, 2020) were divided into two groups-periodontal disease (PD) and healthy control (HC)-according to our predetermined criteria. The mean age of the HC group was 34.4 ± 7.1 years, and the mean age of the PD group was 43.7 ± 8.2 years.…”
Section: Datasets For Analysismentioning
confidence: 99%
“…found (Liu et al, 2020;Schlafer et al, 2010). Thus, F. alocis is strongly associated with periodontitis as a key player in biofilm formation (Aruni et al, 2011;Chen et al, 2015;Naginyte et al, 2019;Wang et al, 2013).…”
Section: Bacterial Killingmentioning
confidence: 90%
“…While there is a high incidence of F. alocis in periodontitis patients, there is a complete absence or low number detected in healthy patients, designating F. alocis as a crucial marker for periodontitis along with P. gingivalis , T. denticola, and T. forsythia (Ahmed et al., 2009; Deng et al., 2017; Ikeda et al., 2019; Kumar et al., 2003, 2006; Schlafer et al., 2010; Schulz et al., 2019). In the oral cavity, F. alocis forms biofilms in close proximity to the soft tissue where some traditional pathogens like T. denticola are also found (Liu et al., 2020; Schlafer et al., 2010). Thus, F. alocis is strongly associated with periodontitis as a key player in biofilm formation (Aruni et al., 2011; Chen et al., 2015; Naginyte et al., 2019; Wang et al., 2013).…”
Section: Filifactor Alocis and Peptoanaerobacter Stomatis: Finding Thmentioning
confidence: 99%
“…In this context, it is significant that the periodontal pathogens Porphyromonas gingivalis and Treponema denticola are predominantly located in deep periodontal pockets at depths of more than 4 mm (52). Furthermore, these pathogens are found together with other periodontal pathogens in microcolony blooms in the biofilm surface layer adjacent to the epithelial lining at the base of deep pockets (52)(53)(54)(55)(56). This positioning and colocalization would advantage them in terms of release of outer membrane vesicles loaded with virulence factors into the subjacent tissue and access to the exudate from that inflamed tissue as well as being consistent with the established mutualistic symbiosis and pathogenesis displayed by these species (55,(57)(58)(59).…”
Section: Opportunistic Polymicrobial Infectionmentioning
confidence: 99%